2002
DOI: 10.1046/j.1469-0705.2002.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Can the degree of retrograde diastolic flow in abnormal umbilical artery flow velocity waveforms predict pregnancy outcome?

Abstract: The A/B or C/D ratio can be used for quantification of the reverse end-diastolic flow waveforms in the umbilical artery and may offer additional information to the evaluation of fetal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…Vascular diseases due to preeclampsia, diabetes mellitus, renal disease or collagen vascular disease are the most common causes of IUGR [5,109]. There is good evidence from hemodynamic studies that the blood supply to the fetoplacental unit is imparied in preeclampsia and SGA and that physiological changes in the spiral arteries are restricted to the decidual segment in such cases [110].…”
Section: Diseases Of the Immune And Vascular System Including Preeclmentioning
confidence: 98%
“…Vascular diseases due to preeclampsia, diabetes mellitus, renal disease or collagen vascular disease are the most common causes of IUGR [5,109]. There is good evidence from hemodynamic studies that the blood supply to the fetoplacental unit is imparied in preeclampsia and SGA and that physiological changes in the spiral arteries are restricted to the decidual segment in such cases [110].…”
Section: Diseases Of the Immune And Vascular System Including Preeclmentioning
confidence: 98%
“…Such outcomes include the risk for stillbirth and neonatal death and the risk for peripartum acidemia and asphyxia, which have been related to poor neurodevelopment9, 10. Qualitative analysis of the UA waveform is easily accomplished and UA‐AREDV is predictive of critical short‐ and long‐term outcomes in IUGR fetuses11–14. The ability of venous Doppler to identify progressive fetal compromise has been demonstrated by several investigators5, 15–19.…”
Section: Introductionmentioning
confidence: 99%
“…Various workers have noticed in fetuses with abnormal umbilical artery Doppler velocimetry, a similar poor perinatal outcome. 19,23,24 Mothers of small for gestational age babies with abnormal Doppler studies were more likely to have history of obstetric complications in the previous pregnancy as observed by McCown et al 19 They had high incidence of delivering small for gestational age babies, gestational hypertension, and history of perinatal death in the previous pregnancy.…”
Section: Discussionmentioning
confidence: 50%
“…25 Brodszki et al analyzed the outcome of 44 fetuses with REDF and found a perinatal mortality of 59%. 24 In a study on the role of umbilical artery Doppler to predict adverse perinatal outcome in women with preeclampsia Yoon et al 26 reported, that when gestational age at birth and pre-eclampsia were controlled for, an abnormal umbilical artery Doppler study was still a significant independent predictor of adverse perinatal outcome. Present study underlines the existence of a strict correlation between umbilical Doppler velocimetry and an increased incidence of perinatal complications in IUGR fetuses, in consonance with the study of Soregaroli et al 27 Similar results were drawn by Baschat et al when they looked at the umbilical artery resistance to determine Rashmi L et al Int J Reprod Contracept Obstet Gynecol.…”
Section: Discussionmentioning
confidence: 99%